Comparative morphological and morphometrical studies on the kidney in broiler chicken and broiler duck - K.P. Deepa; A.R. Sreeranjini; C.B. Soumya (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present study was conducted on the kidneys of six each of adult broiler chicken and broiler ducks. The colour of kidney in chicken was reddish brown while in duck it was slightly greyish. In both broiler chicken and broiler duck, each kidney was incompletely divided into three lobes; cranial, middle and caudal of which caudal lobes were the largest. The shapes of kidney lobes in broiler chicken and duck showed some differences. The kidneys of broiler duck were larger than that of broiler chicken. Length of three lobes on both sides in chicken showed significant difference (P<0.01) while in broiler duck, there was no significant difference in the length of cranial and middle lobes. But, the length of both these lobes differed significantly from that of the caudal lobe (P<0.01). Total weight of kidney as well as total weight of right and left kidneys in chicken showed significant correlation with the body weight at 0.05 percent level while these parameters in ducks showed a significant correlation with the body weight at 0.01 percent level. Except in the case of the width, all other parameters like length, width, thickness and weight of right and left kidneys in chicken and duck showed significant difference at 1 percent level.